2014
DOI: 10.1183/09031936.00175113
|View full text |Cite
|
Sign up to set email alerts
|

The identification of tuberculosis biomarkers in human urine samples

Abstract: We aimed to determine whether shotgun proteomic approaches could be used to identify tuberculosis (TB)-specific biomarkers in the urine of well-characterised patients with active TB versus no TB.Patients with suspected TB (n563) were classified as: definite TB (Mycobacterium tuberculosis positive culture, n521); presumed latent-TB infection (LTBI) (M. tuberculosis negative culture, no radiological features of active TB, a positive QuantiFERON-TB Gold In-Tube (QFT-IT) test and a positive T-SPOT.TB test, n524); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 28 publications
0
52
0
Order By: Relevance
“…In latent TB, Young et al found 6 mycobacterial proteins that were present in urine of HIV uninfected patients which suggests that products other than LAM may be useful for measuring bacterial load over a wide dynamic range, but these require verification in longitudinal studies [46]. …”
Section: Pathogen Based Models and Biomarkersmentioning
confidence: 99%
“…In latent TB, Young et al found 6 mycobacterial proteins that were present in urine of HIV uninfected patients which suggests that products other than LAM may be useful for measuring bacterial load over a wide dynamic range, but these require verification in longitudinal studies [46]. …”
Section: Pathogen Based Models and Biomarkersmentioning
confidence: 99%
“…In this respect, urine has been regarded as the most preferred source of diagnostic biomarkers due to its ease of collection and reduced need for pretreatment compared with other sources. Young et al recently reported the identification of tuberculosis protein biomarkers in human urine samples and concluded that 3 of 10 mycobacterial proteins identified in the urine of TB patients are promising biomarkers for POC diagnostic testing for TB (2). The Campos-Neto group reported a list of TB-diagnostic urine biomarkers (3), among which the Rv1681 protein was clinically validated with sensitivity (44%) for TB diagnosis(4).…”
mentioning
confidence: 99%
“…Because urine is a top-priority biomarker source for point-of-care (POC) testing, systematic approaches for identifying tuberculosis antigens in human urine samples have recently been made (2)(3)(4). Lipoarabinomannan (LAM) is one of the best known biomarkers found in urine, and the assay for detecting LAM in the urine of TB patients is commercially available (5)(6)(7).…”
mentioning
confidence: 99%
“…Extensive reviews of the translational research progress in the urinary proteomic field have been published [2, 41, 49-51]. Potential urinary biomarkers are being discovered in a variety of non-kidney associated diseases including acute appendicitis [52, 53], infectious diseases such as Tuberculosis [54], Chagas Disease and Lyme Disease [55-57], cancer [49, 50, 58-61], cardiovascular disease [62-64], and aging [65, 66]. Selected examples of the progress in urinary protein identification are described below, highlighting a) improvements in mass spectrometry-based urinary proteomic discovery, b) the number of identifiable proteins, and c) pathophysiologic associations over the last decade.…”
Section: Summary Of Urinary Proteomic Biomarker Discovery To Datementioning
confidence: 99%